LANDASAN FILOSOFIS UNTUK KONSTRUKSI AKUNTANSI SYARIAH - Dimyati; Ahmad, Zakiyyah Ilma; Munir, Isa Sirojul (TIJAROTANA : Jurnal Ekonomi Dan Bisnis Syariah, 2023)
This study basically aims to ccntrib lte to the Islamic accounting are looking shape with sides uncover Islam that can be used as a basis and the philosophical foundations for the constriction of Islamic accounting. The discussion was conducted with tile approach of Islam as a religion tI1at brings the mission i”nitInatan li uI-‹hath in have a clear concept of the position of man as caliph on earth who carry out the mandate of his. In carrying out is duties as caliph. all human activity should be manifested as a form of worship to H iin in order to acIiieve fortune and happiness (Malali) both in this world and in the hereafter. From the results of this studi can be drawn a concept that cam be a pIiilosoph ical basis for Islamic accounting. The concept is: the concept of empire. the concept of trusteeship, the concept of worship, and the concept of falâh. Furthermore, the problem of recording itself the concept of computation and muhasabah which is the implementation of “Tl1e Lord of accounting" of all human activity in the world. These concepts will eventually animate the presence of all accounting mandate has dimension of accountability and the metaphor that the mandate will born an equitableaccotinting.